2005
DOI: 10.4012/dmj.24.456
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study on Marginal and Internal Fit of CAD/CAM All-ceramic Crowns

Abstract: The purpose of this study was to evaluate the marginal and internal fit of all-ceramic crowns fabricated using the Decsy CAD/CAM system.A master die of maxillary first premolar was measured, and experimental crowns were fabricated. Four conditions were established by combining two convergence angles (4° and 12° ) of the abutment with two different luting space settings (15 pm and 55 ;u m) . The results showed that the experimental crowns had a marginal gap of 42 to 56 pm. When the luting space setting was 15 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(192 citation statements)
references
References 16 publications
6
180
1
2
Order By: Relevance
“…[14][15][16][17][18] The adaption of the restoration to the preparation with regard to marginal and internal fit has been found to be clinically reliable in numerous studies. [19][20][21][22][23] mm. 24 Relatively large internal gaps can result from the milling process, 25 but gaps of up to 150 mm are clinically tolerable.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] The adaption of the restoration to the preparation with regard to marginal and internal fit has been found to be clinically reliable in numerous studies. [19][20][21][22][23] mm. 24 Relatively large internal gaps can result from the milling process, 25 but gaps of up to 150 mm are clinically tolerable.…”
Section: Discussionmentioning
confidence: 99%
“…The CEREC ® system has been continually improved in terms of both apparatus and software. Numerous reports have been published on this system, with satisfactory long-term results [17][18][19] . A recent iteration of the system can fabricate not only original inlays and onlays, but also crowns and the cores/frameworks of FPDs in both clinical and laboratory settings.…”
Section: Application Of Cad/cam At the Dental Chair-side In A Clinicmentioning
confidence: 99%
“…While a clinically acceptable range of marginal discrepancies is advised to be less than 120 µm, 1 in CAD/CAM or copy-milling systems, the marginal opening has been reported to range between 60 µm and 300 µm. [2][3] Several in vitro studies demonstrated that the marginal adaptation of metal-ceramic FPDs is influenced by the type of cervical finish line, shrinkage after firing procedures of the veneering ceramic, 4-5 differences in thermal expansion coefficients of the framework and veneering ceramic and, most importantly, the amount of circumferential ceramic thickness of the substructure. 6 However, the results on the effect of finish line design on the marginal discrepancies are controversial in the dental literature.…”
Section: Introductionmentioning
confidence: 99%